(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of tongue-twisters in the oral folklore of Turkic peoples, focusing on speech development, pronunciation exercises, and cultural-symbolic content. It demonstrates that tongue-twisters are significant not only as phonetic exercises but also as artistic and aesthetic tools